Supporting Students with Visual Impairments Who Are Culturally and Linguistically Diverse: The Role of the Cultural Liaison Within Educational Teams. (July 2020) - Gee, Stephanie; Zebehazy, Kim T.
Introduction: This study explored the role of the cultural liaison on educational teams that support families from culturally and linguistically diverse (hereafter, diverse) backgrounds who have a child with visual impairment. Methods: Focus groups were conducted with teachers of students with visual impairments, cultural liaisons, and classroom teachers, all who had worked with diverse families and students with visual impairments in an urban Canadian school district. Transcripts of the focus groups were coded for common and divergent themes within and across groups. Results: The groups identified a need for better understanding the role of the cultural liaison, clearer communication in the translation process including messages that may be lost in translation, and more opportunities for teachers of students with visual impairments and classroom teachers to connect with cultural liaisons to develop cultural competency. Discussion: The findings highlight the importance of having access to cultural liaisons and the need to make sure all members are clear about their roles. Cultural liaisons may need additional support about resources from teachers of students with visual impairments, while those same teachers would benefit from understanding the parent perspective on visual impairment. Implications for practitioners: Classroom teachers and teachers of students with visual impairments may want to seek out professional development from cultural liaisons. Teachers of students with visual impairments can provide cultural liaisons with a list of common visual impairment terms to allow time for appropriate translation and questions before a meeting. Cultural liaisons may want to ensure that differing cultural viewpoints of the family are communicated clearly to team members and vice versa.